ijps 2019
DOI: 10.36468/pharmaceutical-sciences.598
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of a Phospholipid Complex for Effective Delivery of Capsaicin

Abstract: Cancer is the main causes of morbidity throughout the world [1][2] . Among the different cancers, breast cancer is the second most important cause of cancer death. Though significant progress has been made in breast cancer treatment, only a few patients benefit from breast cancer by adjuvant chemotherapy and most patients with metastatic cancer are resistant to chemotherapy [3] . In addition, chemotherapy causes acute and chronic toxicities that include sterility, congestive heart failure, osteoporosis and neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…DSC curves obtained for pure CAP or CUR give acuminate single peaks at 66.63 ± 0.01°C and 174.56 ± 0.02°C with an enthalpy of Δ H = 73.85 ± 1.15 J/g and Δ H = 124.97 ± 0.69 J/g, respectively. This concurs with previous values reported in the literature ( 51 , 52 ) and suggest the additional peaks observed in HACS-CAP and HACS-CUR arise from some non-complexed CAP or CUR.…”
Section: Resultssupporting
confidence: 93%
“…DSC curves obtained for pure CAP or CUR give acuminate single peaks at 66.63 ± 0.01°C and 174.56 ± 0.02°C with an enthalpy of Δ H = 73.85 ± 1.15 J/g and Δ H = 124.97 ± 0.69 J/g, respectively. This concurs with previous values reported in the literature ( 51 , 52 ) and suggest the additional peaks observed in HACS-CAP and HACS-CUR arise from some non-complexed CAP or CUR.…”
Section: Resultssupporting
confidence: 93%
“…The reason for the enhanced oral bioavailability of capsaicin‐PVP electrosprayed complex may be ascribed to increased solubility of capsaicin in the gastrointestinal tract. The addition of phospholipids in the prescription could make it easy for the drug to penetrate the biological membrane (Mondal et al., 2019; Weng et al., 2019; Zhang et al., 2015). As a component of the lipid membrane, phospholipid has a high affinity for the cell membrane, which can promote absorption of the drug and also improve the bioavailability of capsaicin.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for the enhanced oral bioavailability of capsaicin-PVP electrosprayed complex may be ascribed to increased solubility of capsaicin in the gastrointestinal tract. The addition of phospholipids in the prescription could make it easy for the drug to penetrate the biological membrane (Mondal et al, 2019;Weng et al, 2019;Zhang et al, 2015).…”
Section: In Vivo Administration Study In Ratsmentioning
confidence: 99%
“…Kumar, et al (2021) conducted a study in which a taxifolin ethyl acetate fraction derived from Cedrus deodara bark extract was loaded into a phytosome delivery system, with aims to evaluate the antioxidant and anticancer activity of taxifolin [50]. Phytosomes can increase the lipophilicity of the active compound so that they enhance the absorption of the active substance and increase its ability to cross biological membranes [66]. Based on the research of Kumar, et al (2021), phytosomes showed high antioxidant activity with a lower IC50 value compared to the ethyl acetate and the standard.…”
Section: Phytosomes Increasing the Activity Of Phytochemical Compoundsmentioning
confidence: 99%